Proximal Aortic Neck Progression: Before and After Abdominal Aortic Aneurysm Treatment - Filis, Konstantinos A.; Galyfos, George; Sigala, Fragiska; Tsioufis, Konstantinos; Tsagos, Ioannis; Karantzikos, Georgios; Bakoyiannis, Christos; Zografos, George (Frontiers in Surgery, 2017)
Several risk factors including short or highly angulated proximal aortic neck have been associated with long-term outcomes after endovascular or open abdominal aortic aneurysm (AAA) repair. However, research data have emerged recently concerning the behavior of proximal aortic neck, and several authors have tried to evaluate this behavior after endovascular or open repair. Additionally, computed tomography angiography (CTA) remains the golden standard for detecting and observing the morphology of an AAA, both before and after treatment. Moreover, the question of whether the proximal neck’s progression independently affects postoperative morbidity and reintervention risks still remains. Therefore, this focused review aims to present all relevant data on the behavior of an AAAs neck, based on CTA imaging before and after repair, in order to produce useful conclusions for future clinical practice.